2008
DOI: 10.1111/j.1469-0691.2008.01992.x
|View full text |Cite
|
Sign up to set email alerts
|

Infection control measures to limit the spread of Clostridium difficile

Abstract: Clostridium difficile-associated diarrhoea (CDAD) presents mainly as a nosocomial infection, usually after antimicrobial therapy. Many outbreaks have been attributed to C. difficile, some due to a new hyper-virulent strain that may cause more severe disease and a worse patient outcome. As a result of CDAD, large numbers of C. difficile spores may be excreted by affected patients. Spores then survive for months in the environment; they cannot be destroyed by standard alcohol-based hand disinfection, and persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
184
2
11

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(203 citation statements)
references
References 170 publications
(269 reference statements)
6
184
2
11
Order By: Relevance
“…This result is consistent with reports of similar outbreaks in which such interventions were enforced in conjunction with early detection of infection (2,20).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This result is consistent with reports of similar outbreaks in which such interventions were enforced in conjunction with early detection of infection (2,20).…”
Section: Discussionsupporting
confidence: 82%
“…This study also confirms the importance of rapid implementation of such interventions (20) to reduce transmission of the disease and the impact of the outbreak.…”
Section: Discussionsupporting
confidence: 61%
“…Additionally; it has been shown that the skin surfaces of patients with CDI diarrhea that resolved 2 weeks before is still contaminated with C. diffi cile that may be transferred to an examining gloved hand ( 177 ). One recommendation is to maintain contact precautions for 48 h aft er diarrhea ceases ( 178 ). Some institutions have implemented contact precautions for the duration of hospitalization as part of their infection control interventions for CDI ( 168 ).…”
Section: Management Of CDI and Co-morbid Conditionsmentioning
confidence: 99%
“…Infection is often chronic and difficult to eradicate (O'Brien et al, 2007). C. difficile is transmitted as dormant endospores that are highly resistant to killing by heat, antibiotics, oxidizing agents, UV radiation and many other treatments that are usually effective for killing bacteria (Vonberg et al, 2008;Setlow, 1995). C. difficile spores germinate in the intestine to produce vegetatively growing cells capable of producing toxins A and B, which have been implicated in disease progression and severity (Bartlett et al, 1977;McDonald et al, 2005).…”
Section: Introductionmentioning
confidence: 99%